Kode Etik Tenaga Pendidik Dalam Meningkatkan Mutu Pendidikan - Heni Juniyanti; Astuti Darminyanti; Saprialman Saprialman (Peneliti.net, 2023)
code of ethics and teacher professionalism in improving the quality of education, in this study the authors used a qualitative descriptive analysis, namely the library research approach. The results of this study are being able to know the nature of the teacher because the teacher is the person who plays a role in the effort to form human potential by developing all the talents that exist in students. Teachers must also be able to play an active role in educating students and be able to place their position as teaching staff. Teacher competence in improving the quality of education is divided into four parts, namely pedagogic competence, personal competence, social competence and professional competence. The type of teacher is to have a commitment to improve the quality of education, faith, piety, and noble character. Teachers who have good academic qualifications, competencies and educational backgrounds have responsibility for carrying out professional duties and guaranteeing legal protection. In fact, the profession held has the authority to regulate those related to teacher professionalism. The challenges faced by teachers today are the rapid development of information technology, decentralization and centralization of education.